Effects of Kojic Acid-mediated Sonodynamic Therapy as a Matrix Metalloprotease-9 Inhibitor against Oral Squamous Cell Carcinoma: A Bioinformatics Screening and In Vitro Analysis - Pourhajibagher, Maryam; Alaeddini, Mojgan; Etemad-Moghadam, Shahroo; Parker, Steven; Bahador, Abbas (Current Drug Discovery Technologies, 2024)
Background: Oral squamous cell carcinoma (OSCC) is a type of cancer that is responsible for a significant amount of morbidity and mortality worldwide. Researchers are searching for promising therapeutic methods to manage this cancer. In this study, an in silico approach was used to evaluate the activity of sonodynamic therapy (SDT) based on the use of Kojic acid as a sonosensitizer to inhibit matrix metalloprotease-9 (MMP-9) in OSCC. Materials and Methods: The three-dimensional structure of MMP-9 was predicted and validated by computational approaches. The possible functional role of MMP-9 was determined in terms of Gene Ontology (GO) enrichment analysis. In silico, molecular docking was then performed to evaluate the binding energies of Kojic acid with MMP-9, and ADME parameters and toxicity risks were predicted. The pharmacokinetics and drug-likeness properties of Kojic acid were assessed. Moreover, after the determination of the cytotoxicity effect of Kojic acid-mediated SDT, the change of mmp-9 gene expression was assessed on OSCC cells. Results: The results of the study showed that Kojic acid could efficiently interact with MMP-9 protein with a strong binding affinity. Kojic acid obeyed Lipinski’s rule of five without violation and exhibited drug-likeness. The cytotoxic effects of Kojic acid and ultrasound waves on the OSCC cells were dose-dependent, and the lowest expression level of the mmp-9 gene was observed in SDT. Conclusions: Overall, Kojic acid-mediated SDT as an MMP-9 inhibitor can be a promising adjuvant treatment for OSCC. The study highlights the potential of In silico approaches to evaluate therapeutic methods for cancer treatment.
Keywords: sonodynamic therapy